Persepsi Terhadap Asertivitas Pimpinan dan Keterikatan Kerja Karyawan - Yoga Rendy Riandana; Nur Pratiwi Noviati (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2014)
The aim of this research was to empirically examine the correlation between employee's perception about their leader's assertiveness and their work engagement level. The level ofperception about assertiveness of leaders on employees is directly proportional to the work engagement level. Subjects in this study were 70 employees of PTX. The measurement tool used is Work Engagement Scale which adapted from aspect of Schaufeli andBakker's theory. Whereas, perception on leader's assertiveness scale was based on the theory by Eisler, Miller & Hersen, Johnson & Pinkton. Statistic method by SPSS ¡5.00 for windows was applied to analyze data. The product moment correlation from Pearson showed that correlation coefficient r= 0.768, p= 0.000, p<0.01. The test result showed a significant positive correlation between employee's perception about assertiveness of their leader and work engagement level on them. Then, the proposed hypothesis is accepted. Keywords: work engagement, employee's perception about assertiveness oftheir leader.